Implication of the anterior commissure in the allocation of attention to action - Winter, Taylor J.; Franz, Elizabeth A. (Frontiers in Psychology, 2014)
Our recent target article on the allocation of attention to action (herein called the AAA model; Franz, 2012) considered implicated subcortical processes and networks in people with intact corpus callosum and people without a corpus callosum due to commissurotomy or callosotomy. However, a small error in print— namely that the term ‘commissurotomy’ was printed in place of ‘callosotomy’ in some instances—led us to further explore whether any key functional roles have been attributed to the two primary cortical commissures (the anterior and posterior commissures) which remain intact in people with callosotomy, and if so, whether those would be relevant to our current AAA framework. Although existing evidence is sparse, here we consider the hypothesis that the anterior commissure is a remnant fiber tract which has been largely replaced with evolution of the corpus callosum (and we do not herein discuss the posterior commissure further). Indeed, a dearth of studies is available on the anterior commissure, calling the need for further research. Herein, we briefly review literature on the anterior commissure (AC) in humans and then propose a method that might be worthwhile to pursue in future studies.